Experimental Investigation of the Pressure Dependence of Iso-Octane Combustion - Shaqiri, S.; Kaczmarek, D.; vom Lehn, F.; Beeckmann, J.; Pitsch, H.; Kasper, T. (Frontiers in Energy Research, 2022)
Iso-octane is frequently used as a surrogate fuel or as a component in primary reference fuel blends when low-temperature combustion strategies in engines are investigated. To develop control strategies for these engines, the reaction kinetics of iso-octane must be known starting from the low temperatures and intermediate pressures before ignition to the high temperatures and pressures of combustion. This work adds new experimental data sets to the validation data for reaction mechanism development by investigating the oxidation of iso-octane in stoichiometric mixtures in a flow reactor at pressures of p = 1, 10, and 20 bar and 473K ≤ T ≤ 973 K. The experimental data are compared to simulations with recent reaction mechanisms [Atef et al., Combustion and Flame 178, (2017), Bagheri et al., Combustion and Flame 212, (2020), Cai et al., Proceedings of the Combustion Institute 37, (2018), Fang et al., Combustion and Flame 214, (2020)]. The comparison between experimental and simulated mole fractions as function of temperature show reasonable agreement for all investigated pressures. In particular, the experimentally observed onset of low-temperature reactivity above a certain pressure, the shift of the negative temperature coefficient (NTC) regime with increasing pressure to higher temperatures, and the acceleration of the high-temperature chemistry are captured well in the simulations. Deviations between experimental and simulated results are discussed in detail for the reactivity of iso-octane and some key intermediates such as 2,2,4,4-tetramethyl-tetrahydrofuran, iso-butene and acetone at low temperatures.